Failure analysis of adhesively bonded joints using a modulatory damage model (vol 163, 108602, 2024) - Khabaz-Aghdam, Ata; Dizaji, Shahram A.; Choupani, Naghdali; Silva, Lucas F. M. da (Pergamon-Elsevier Science Ltd, 2024)
[No abstract available]